PENYEDIAAN FASILITAS PENGELOLAAN SAMPAH DI DESA KERANGGAN – DESA BINAAN UNIVERSITAS SWISS GERMAN [WASTE DISPOSAL FACILITATION FOR DESA KERANGGAN SOCIETY – SWISS GERMAN UNIVERSITY COMMUNITY SERVICE PROJECT] - Alfiandri Alfiandri; Evita Herawati Legowo; Kholis Abdurachim Audah; Muhammad Riyadh Rizky Adam (Universitas Pelita Harapan, 2018)
Road map the community service of Swiss German University activities in 2016 until 2020 about manage of non-organic wasted. In addition, Keranggan village is used as the pilot project to implement the program of non-organic waste management which is located in district of Tangerang, Banten, Indonesia. Swiss German University provides non-organic waste tool to facilitate burn non-organic waste such as, banana peels and humid waste are name of fews and its names as traditional incinerator. The objective to develop this tool is used the burn the waste and the waste may use for fertilizer and bricks manufacturer. At the same time, to educate the villagers to look after their environments and lead to life clean and healthy. The traditional incinerator developed for home scale that could cover 10 to 15 house waste. In addition, Swiss German University provided three units and put in the different area in the Keranggan village.